Panenteric capsule endoscopy versus ileocolonoscopy plus magnetic resonance enterography in Crohn’s disease: a multicentre, prospective study - Stanley Cohen; Jordi Rimola; Joel G Fletcher; Monika Fischer; David Henry Bruining; Salvatore Oliva; Mark R Fleisher; Linda Cummings; Mukund Venu; Laurel Fisher; Tuba Esfandyari; Kara De Felice; et al. (BMJ Open Gastroenterology)
Introduction Crohn’s disease diagnosis and monitoring remains a great clinical challenge and often requires multiple testing modalities. Assessing Crohn’s disease activity in the entire gastrointestinal (GI) tract using a panenteric capsule endoscopy (CE) system could be used as an alternative to colonoscopy and cross-sectional imaging. This study assessed the accuracy and safety of panenteric CE in Crohn’s disease as compared with ileocolonoscopy (IC) and/or magnetic resonance enterography (MRE).Methods A prospective, multicentre study was performed in subjects with established Crohn’s disease. Individuals with proven small bowel patency underwent a standardised bowel preparation, followed by CE ingestion and IC either the same or following day. MRE, IC, and CE interpretations were performed by blinded central readers using validated scoring systems. The primary endpoint was the overall sensitivity of CE vs MRE and/or IC in Crohn’s disease subjects.Results Study enrolment included 158 subjects from 21 sites in the USA, Austria, and Israel. Of those, 99 were included in the analysis. Imaging modality scores indicated none to mild inflammation in the proximal small bowel and colon, but discrepant levels of inflammation in the terminal ileum. Overall sensitivity for active enteric inflammation (CE vs MRE and/or IC) was 94% vs 100% (p=0.125) and specificity was 74% vs 22% (p=0.001). Sensitivity of CE was superior to MRE for enteric inflammation in the proximal small bowel (97% vs 71%, p=0.021), and similar to MRE and/or IC in the terminal ileum and colon (p=0.500–0.625). There were seven serious adverse advents of which three were related to the CE device.Conclusion Panenteric CE is a reliable tool for assessing Crohn’s disease mucosal activity and extent compared with more invasive methods. This study demonstrates high performance of the panenteric CE as compared to MRE and/or IC without the need for multiple tests in non-stricturing Crohn’s disease.Trial registration number ClinicalTrials.gov NCT03241368